Homo- and Heterobimetallic Complexes in Catalysis Cooperative Catalysis - Kalck, Philippe; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
The series Topics in Organometallic Chemistry presents critical overviews of research results in organometallic chemistry. As our understanding of organometallic structure, properties and mechanisms increases, new ways are opened for the design of organometallic compounds and reactions tailored to the needs of such diverse areas as organic synthesis, medical research, biology and materials science. Thus the scope of coverage includes a broad range of topics of pure and applied organometallic chemistry, where new breakthroughs are being achieved that are of significance to a larger scientific audience. The individual volumes of Topics in Organometallic Chemistry are thematic. Review articles are generally invited by the volume editors. All chapters from Topics in Organometallic Chemistry are published OnlineFirst with an individual DOI. In references, Topics in Organometallic Chemistry is abbreviated as Top Organomet Chem and cited as a journal.
Bimetallic homogeneous hydroformylation -- Binuclear iridium complexes in catalysis -- Reactivity and catalysis at sites trans to the [Ru-Ru] bond -- Alkyne activation using bimetallic catalysts,- "Early-Late" heterobimetallic catalysis and beyond -- The catalytic binuclear elimination reaction: importance of non-linear kinetic effects and increased synthetic efficiency -- Biomimetic complexes for production of dihydrogen and reduction of CO2.
Keywords: Organometallic chemistry .; Catalysis; Chemistry, Technical; Organometallic Chemistry; Catalysis; Industrial Chemistry